Pharmacological dose of alpha-tocopherol induces cardiotoxicity in Wistar rats determined by echocardiography and histology - Nascimento, Maria Carolina M. O. [UNESP]; Matsubara, Beatriz Bojikian [UNESP]; Matsubara, Luiz Shiguero [UNESP]; Corrêa, Camila Renata [UNESP]; Pereira, Elenize J. [UNESP]; Moreira, Priscila L. [UNESP]; Carvalho, Flavio A. [UNESP]; Burini, Caio H. [UNESP]; Padovani, Carlos Roberto [UNESP]; Yeum, Kyung-Jin; Ferreira, Ana Lúcia dos Anjos [UNESP] (Sage Publications Ltd, 2011)
The effect of pharmacological dose of cc-tocopherol on heart health was determined in Wistar rats. Animals were randomly assigned to either C (control, n = II) or E (cc-tocopherol, n = II) group. Animals received corn oil (C) or alpha-tocopherol dissolved in corn oil (250 mg alpha-tocopherol/[kg body wt/day]) (E) by gavage for a 7-week period. Rats underwent echocardiogram and were analyzed for cardiomyocyte histology and cardiac cc-tocopherol absorption at the end of the study period. As compared to the C group, alpha-tocopherol-supplemented group showed significantly (p < 0.05) lower body weight (E, 412.8 g vs C, 480.3 g) and total cardiac weight (E, 0.94 g vs C, 1.08 g); cardiomyocyte histological impairment; smaller left ventricle (LV) (LV end-diastolic diameter (E, 7.22 mm vs C, 7.37 mm), lower LV systolic [left ventricle fractional shortening (E, 47.6% vs C, 53.6%) and ejection fraction ratio (E, 85.4 vs C, 89.9)] and diastolic [early peak velocities of diastolic transmitral flow (E, 64.6 cm/sec vs C, 75.1 cm/sec)] function. The alpha-tocopherol uptake in target tissue was confirmed by determination of alpha-tocopherol concentration medians in cardiac tissue (E, 109.91 nmol/kg vs C, 52.09 nmol/kg). The current study indicates that pharmacological dose of alpha-tocopherol supplementation can induce cardiotoxicity in healthy rats.
Keywords: alpha-tocopherol; cardiotoxicity; rat; Doppler-echocardiogram